2009
DOI: 10.1055/s-0029-1224721
|View full text |Cite
|
Sign up to set email alerts
|

Infektiologische Bedeutung von Raumlufttechnischen Anlagen (RLTA) in Operations- und Eingriffsräumen

Abstract: Surgical teams need to breathe air that is conducive to their health. An adequate exchange of air ensures oxygen supply, the ventilation of humidity, smells, toxic substances, especially narcotic gases and surgical smoke, pathogens and particles. With regard to the infection risk, DIN 1946 / 4 -differentiates between operation theaters with the highest demand for clean air (operation room class I a), operation theatres with a high demand (operation room class I b) and rooms within the operation theatres withou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 6 publications
0
2
0
1
Order By: Relevance
“…However, this study generated a lot of debate, at least in Germany. [9][10][11] One of the major discussion points was the hypothesis that only ceiling distribution systems with a size of 2 or larger 3.2 m # 3.2 m work appropriately and that we did not consider the size of the LAF ceilings. 9,10 Therefore, we decided to investigate the association between SSI rates and the availability of LAF in the operating rooms again for the next 5-year period, with a special focus on ceiling size.…”
mentioning
confidence: 99%
“…However, this study generated a lot of debate, at least in Germany. [9][10][11] One of the major discussion points was the hypothesis that only ceiling distribution systems with a size of 2 or larger 3.2 m # 3.2 m work appropriately and that we did not consider the size of the LAF ceilings. 9,10 Therefore, we decided to investigate the association between SSI rates and the availability of LAF in the operating rooms again for the next 5-year period, with a special focus on ceiling size.…”
mentioning
confidence: 99%
“…New, albeit retrospective non-controlled studies showed no protective influence in comparison to TML (mixed flow ventilation) [ 13 ], [ 14 ], [ 15 ], [ 16 ], [ 17 ]. All studies are marked by a number of limitations [ 18 ], [ 19 ], and thus do not lead to conclusive evidence at this point in time [ 20 ].…”
Section: Recommendations For User Unitsmentioning
confidence: 99%
“…Allerdings spielt insgesamt betrachtet die Raumluft bei den meisten operativen Eingriffen als eigenständiges Erregerreservoir keine wesentliche Rolle, und selbst bei orthopädischen Implantationsoperationen kann sie nicht als Haupterregerreservoir betrachtet werden 3 ( 7,8,9,10,11 ). Auch die KRINKO kommentiert, dass aufgrund des infektionsprophylaktischen Effekts eine Differenzierung in Raumklasse Ia und Ib nicht gerechtfertigt ist 2 .…”
Section: Raumlufttechnikunclassified